Effect of Green Tea Mucoadhesive Paste on Recurrent Aphthous Stomatitis Treatment - Atekeh Movaghari pour; Payam Khazaeli; Nazanin Kamyab; Mahsa Pourzamani; Fatemehsadat Moeinzadeh; Mahmood Sheikh Fathollahi (Mashhad University of Medical Sciences, 2020)
Introduction: Recurrent aphthous stomatitis (RAS) is a common oral disease, which presents as painful and recurrent single or multiple ulcers in the oral mucosa. This condition is an idiopathic disease and has no definitive cure; accordingly, it is very important to find a drug to control the disease. Since green tea is a rich source of antioxidant and has an anti-inflammatory effect, this study was aimed to determine the effect of a mucoadhesive paste, containing green tea extract, on RAS. Materials and Methods: This double-blind, placebo-controlled clinical trial was conducted on 52 patients with RAS. The study population was randomly divided into two groups of intervention (using a mucoadhesivepaste containing green tea extract) and placebo (using a mucoadhesive paste without drug). They used mucoadhesive paste three times a day for 10 days. Pain severity was measured based on the visual analog scale at the beginning of the study (day zero) and 1, 6, and 10 days post-intervention. In addition, the lesion size was measured using a probe. The data were analyzed in SPSS software (version 21) using two-way repeated measures ANOVA. Results: According to the results, pain and recovery time were significantly lower in the intervention group than in the control group (p < /em><0.05). However, the ulcer size did not show any statistically significant difference between the two groups over time (p < /em>>0.05). Conclusion: As the findings indicated, the use of mucoadhesivepaste, containing green tea extract, can reduce the pain severity and healing time of RAS. However, it was not effective in reducing the size of lesions.